Design and fabrication of engine cooling water conditioning system - 463434 Nor Azizy Suratanin (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia,2002